2002
DOI: 10.1103/physreve.65.031908
|View full text |Cite
|
Sign up to set email alerts
|

Photon-density waves in macroscopic and microscopic plane-parallel scattering samples

Abstract: We investigate the validity of the Boltzmann equation to predict the reflection and transmission coefficients for an intensity modulated laser beam passing through a microscopic medium consisting of discrete scatterers. For a one-dimensional model system we demonstrate that the Boltzmann equation works remarkably well for small modulation frequencies, even to describe a medium comprised of only 10 scatterers. Discrepancies can be found only if the modulation wavelength of the laser intensity is commensurate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Let us now investigate the Lorentz contraction for a more complicated case in which the spin variables are coupled directly to a static homogeneous magnetic field along the z-direction. In order to bring the electron to a high speed orbit [10] we have used an additional timedependent electric field, E(t) = E sin(ω L t) e x , whose frequency ω L was chosen to be close to the cyclotron frequency = B/c associated with the magnetic field of B = Be z . To remain focused on the effect of the Lorentz spin contraction, we exclude here for better clarity any relativistic effects on the orbital motion.…”
Section: Non-relativistic Orbits With Direct Field-spin Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us now investigate the Lorentz contraction for a more complicated case in which the spin variables are coupled directly to a static homogeneous magnetic field along the z-direction. In order to bring the electron to a high speed orbit [10] we have used an additional timedependent electric field, E(t) = E sin(ω L t) e x , whose frequency ω L was chosen to be close to the cyclotron frequency = B/c associated with the magnetic field of B = Be z . To remain focused on the effect of the Lorentz spin contraction, we exclude here for better clarity any relativistic effects on the orbital motion.…”
Section: Non-relativistic Orbits With Direct Field-spin Couplingmentioning
confidence: 99%
“…There exist no analytical solutions for the relativistic orbit since the nonlinearity induced by the relativistic resonance makes the system non-integrable and even excites chaotic orbits [13]. Previous works [3,10,14] have shown that the spatial evolution of the wavepacket is characterized by the formation of ring-like probability distributions that rotate around the origin with the period of the laser [15].…”
Section: Relativistic Orbits With Direct Field-spin Couplingmentioning
confidence: 99%